A Review on Advanced Nanomaterials for Antibacterial Applications - Jose, Jephin K.; Cherian, Christie T.; Balachandran, Manoj (Current Nanoscience, 2023)
The management of infectious diseases is one of the major public health challenges of the 21st century. Mutation of the microbes, biofilm formation, and other structural-morphological behaviors have resulted in pathogens acquiring multi-drug resistance. The development of advanced materials that can provide long-lasting and effective protection against harmful microbes is becoming a need of the hour. Biocompatibility, efficient microbial inactivation, thermal and chemical stability of nanomaterials help to reduce the excessive use of antibiotics and, thus, to overcome antimicrobial resistance. Metal and metal oxide nanostructures, graphene, carbon dots, and other two-dimensional materials exhibit excellent antimicrobial properties. This review provides a comprehensive overview of antibacterial mechanisms and factors that help to inactivate the bacteria by nanomaterials. It also points out the enhanced antibacterial behaviors of the modified nanomaterials for future research concerns.
Keywords: Antibacterial